Pengembangan dan Implementasi Chatbot Pelayanan Masyarakat Berbasis Dialogflow di Kelurahan Gebang Putih Surabaya - Nailussa’ada, Nailussa’ada; Martono, Hero Yudo; Yunanto, Andhik Ampuh; Wibowo, Prasetyo; Santoso, Dian Septiani; Prasetyaningrum, Ira; Humaira, Fitrah Maharani; Khoirunnisa, Asy Syaffa; Alfaqih, Wildan Maulana Akbar; Al Falah, Adam Ghazy (El-Mujtama: Jurnal Pengabdian Masyarakat, 2025)
Residents of Gebang Putih, Surabaya, often face challenges in accessing administrative information, such as procedures for creating ID cards, updating family data, and registering for marriage. To address these issues, a chatbot based on Dialogflow was developed and integrated with the Telegram platform and a mobile application called Kagapi. This study included data collection from official government websites, interviews with local office staff, and dataset preparation for chatbot training. The results showed that the chatbot achieved a 92% accuracy rate in understanding and responding to user queries, with an average response time of 2-3 seconds. Integration with the mobile application expanded service features, including online queue management. Testing and evaluation by local office staff and residents indicated that the chatbot improved information accessibility and service efficiency by up to 80%. This chatbot demonstrates the potential to serve as an innovative solution in enhancing public service transparency and accessibility.